ANALISIS LAPORAN KEUANGAN DALAM RANGKA PENYUSUNAN ANGGARAN KAS GUNA PENGAMBILAN KEPUTUSAN PADA PT XYZ - Safri Safri; Iswandir Iswandir (JURNAL MITRA MANAJEMEN, 2019)
The budget is a sum of money spent in a certain period to carry out a program, the company's aging schedule which shifts to a longer time makes the company's cash eroded. Cash budget analysis using the moment method receivable budget shows a bed dept of 1.56%, with revenue and expenditure proceeds from July to December 2018, where in July and August the company's cash is minus, to cover it the company is expected to make short-term loans, with indications with these short-term loans at the end of the month the company's cash will be better.October to December 2018 the sale of the company has been able to cover all expenses, if the company continues to obey what has been planned, the company's cash will be surplus, so it is not burdened with loan payments and interest payments